Hubungan Kepatuhan Konsumsi Kelasi Besi Terhadap Pertumbuhan Anak Dengan Thalassemia - Muhammad Syobri; Festy Ladyani Mustofa; Nia Triswanti (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2020)
Thalassemia is a hereditary synthesis of hemoglobin. Based on data from the Association of Parents of Indonesian Thalassemia Patients known that thalassemia sufferers in Indonesia increased from 4,896(2012) to 9,028(2018). This study aims to determine the relationship between compliance with consumption of iron chelation to the growth of children with thalassemia in thalassemia shelter Bandar Lampung. This research uses correlation analytic method with cross-sectional approach. Sampling uses purposive sampling technique. The sample in this study were children with beta major thalassemia aged 5-10 years who recorded in thalassemia transit home in Bandar Lampung totaling 55 respondents. The results obtained 60% of respondents who have good consumption of iron chelation and who have good growth as much as 76.4% of respondents. Results of the Spearman test found that there is a significant relationship between compliance with consumption of iron chelation to the growth of children with thalassemia (p=0.001). With the correlation coefficient value of 0.419 having a positive sign which means the compliance value of consumption of iron chelation is high, the growth value of thalassemia children is also high, and vice versa if compliance with iron chelation consumption is low, the growth value of thalassemia children is also low.